Density and Distribution of Seagrass in Beruk Island Coastal Waters Rupat Island of Bengkalis Regency Riau Province - Hara, Filio; Mulyadi, Aras; ', Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Seagrasses are plants adapted to live fully in the marine environment. Seagrass plays an important role in coastal areas due to critical habitat for many kinds of marine animals such as fish, molluscs, crustaceans, echinoderms. The research was conducted inJanuary 2015 inBeruk Island Waters in order to know the different of seagrass distribution and density in northern and southern partsof Beruk Island. The method used was line transect and applyingsix stations, namely stations I, II and III in the southern part of Beruk Island and stations IV, V and VI in the northern area of Beruk Island. The results obtained II seagrass species, i.e. Enhalus acoroides and Halophila ovalis.The pattern of distribution of seagrass at southern of Beruk Island was randomized and E. acoroideswas found as the most dominant species. However,the distribution  in northern of Beruk Island was cluster at station IV and V and randomized at station VI with the dominant species wasH. ovalis. The highest E. acoroides density was found in southern of Beruk Island at station II with the total density of 80 individuals/m2.The highest H. ovalis density in northern partof Beruk Island was at station V with the total density of40 individuals/m2. Key Words : Seagrass, Distribution, Density, Beruk Island, Bengkalis